1978
DOI: 10.1159/000225278
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Alcohol Intake Upon the Hepatic Microsomal Carcinogen-activation System

Abstract: Ethanol was administered to mice either by repeated intraperitoneal injection, or orally in the drinking water over an extended period of time. Following intraperitoneal ethanol pre-treatment further groups of mice received an injection of benzo(a)pyrene. Alcohol intake decreased the level of microsomal aryl hydrocarbon hydroxylase which corresponded to the observed decrease in DNA binding of benzo(a)pyrene. In contrast, the number of tumors which developed in the alcohol pre-treated mice exceeded those of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Moreover, chronic ethanol ingestion has a carcinogenic enhancing effect for tumors of various tissues induced by polycyclic hydrocarbons and nitrosamines (2,3). Our laboratory has recently established a biochemical link between alcohol and carcinogen metabolism by reporting a high degree of homology between the major fatty acid ethyl ester (FAEE)' synthase from human myocardium and the glu-tathione (GSH) S-transferases, or GSTs, enzymes that detoxify a wide variety of polycyclic carcinogens and xenobiotics (4).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, chronic ethanol ingestion has a carcinogenic enhancing effect for tumors of various tissues induced by polycyclic hydrocarbons and nitrosamines (2,3). Our laboratory has recently established a biochemical link between alcohol and carcinogen metabolism by reporting a high degree of homology between the major fatty acid ethyl ester (FAEE)' synthase from human myocardium and the glu-tathione (GSH) S-transferases, or GSTs, enzymes that detoxify a wide variety of polycyclic carcinogens and xenobiotics (4).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous experiment [4,5] the effect of alcohol intake upon the enzyme systems concern ed with the activation and detoxication of carcinogens was investigated. It was found that, at the dose levels employed, ethanol decreased DNA binding of benzo(a)pyrene but the number of tumors induced by this carcinogen exceeded those in the control group.…”
Section: Introductionmentioning
confidence: 99%
“…Since FAEE synthase is a very anionic protein and, indeed, was first recognized by its ability to bind tightly to DEAE-cellulose at neutral pH, our studies identify this main FAEE synthase as one of the first members of the acidic class of GSH transferases to be purified to homogeneity. (31,32). Our results suggest that hepatic GSH transferases constitute an important system for ethanol elimination and thus establish a biochemical link between alcohol, xenobiotic, and carcinogen metabolism that must be taken into account in understanding drug-induced hepatic neoplasia.…”
mentioning
confidence: 99%